Propriospinal Neurons: Essential Elements of Locomotor Control in the Intact and Possibly the Injured Spinal Cord - Laliberte, Alex M.; Goltash, Sara; Lalonde, Nicolas R.; Bui, Tuan Vu (Frontiers in Cellular Neuroscience, 2019)
Propriospinal interneurons communicate information over short and long distances within the spinal cord. They act to coordinate different parts of the body by linking motor circuits that control muscles across the forelimbs, trunk, and hindlimbs. Significant loss of motor function can arise when an injury to the spinal cord disrupts the flow of motor commands from the brain and brainstem to spinal motor circuits. However, recovery of lost locomotor function can occur through the formation and activation of circuits formed by spared propriospinal interneurons. In light of progress made in treating lost motor function following spinal cord injury in animal models and human patients, we discuss the role of propriospinal interneurons in the intact spinal cord and describe recent studies investigating the assembly and/or activation of propriospinal circuits to promote recovery of locomotion following spinal cord injury.